Pendidikan Kewarganegaraan Berbasis Karakter melalui Penerapan Pendekatan Pembelajaran Aktif, Kreatif, Efektif dan Menyenangkan - Setiawan, Deny (Universitas Negeri Medan, 2014)
In the new paradigm of civic education, it purposes in forming civil society by empowering citizens in the democratic government. Therefore, the subject of civic education in the primary school should be significantly designed by describing functionally the com-ponents of civic knowledge, civic skills and civic dispositions, so that learners as citizens could be participate actively both in the context ofÂ society in national life, as well as in the context society of global life (desirable personal qualities). In achieving these objectives, character based of civic education should be implemented by the active, creative, effective and joyful learning as an innovative learning.